2020
DOI: 10.1371/journal.pone.0229202
|View full text |Cite
|
Sign up to set email alerts
|

Sleepiness and injury risk in emergency medical service workers in Taiwan

Abstract: Background Insufficient sleep is a common health and safety risk factor in high-impact workplaces where workers are required to take rotating shifts. However, studies on sleepiness-related risks and incidents, particularly among emergency medical services (EMS) workers are limited. Objective This study sought to investigate the prevalence of sleepiness and related workplace incidents among EMS workers. Methods This study utilized a cross-sectional survey design on a convenient sample of 500 EMS workers from 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 48 publications
1
16
1
4
Order By: Relevance
“…[16] Physical and mental fatigue has been shown to affect 50% of EMS personnel in the USA, [18] while excessive daytime sleepiness was experienced by 39.2% of EMS personnel in a study in Taiwan. [35] In comparison, in the present study, difficulty staying awake during a shift was reported by 73.3% of respondents and insomnia by 22.5%, while 10.5% perceived that their insomnia was secondary to stimulant use. Similarly, a study investigating energy drink consumption among medical students and junior doctors in Malta reported that 31.9% of respondents experienced insomnia after consuming energy drinks.…”
Section: Researchcontrasting
confidence: 66%
“…[16] Physical and mental fatigue has been shown to affect 50% of EMS personnel in the USA, [18] while excessive daytime sleepiness was experienced by 39.2% of EMS personnel in a study in Taiwan. [35] In comparison, in the present study, difficulty staying awake during a shift was reported by 73.3% of respondents and insomnia by 22.5%, while 10.5% perceived that their insomnia was secondary to stimulant use. Similarly, a study investigating energy drink consumption among medical students and junior doctors in Malta reported that 31.9% of respondents experienced insomnia after consuming energy drinks.…”
Section: Researchcontrasting
confidence: 66%
“…Evidenciou-se que a sonolência diurna excessiva é comum entre os paramédicos em Taiwan. Esse achado mostra que a sonolência é um fator precipitante de acidentes entre os trabalhadores do serviço médico de emergência 27 .…”
Section: Discussionunclassified
“…A partir desse ponto, foi realizada a análise crítica das 12 publicações resultantes (Figura 1). Em relação aos métodos, a abordagem apresentada pelos trabalhos em seis dos 12 estudos foi a aplicação de instrumentos utilizados para verificação da vigília e da performance cognitiva dos profissionais, alguns dos quais mencionados com maior frequência: Epworth Sleepiness Scale 18,19 , Psychomotor Vigilance Test, Karolinska Sleepiness Scale 20 , Maslach Burnout Inventory 21 . Esses instrumentos foram utilizados em estudos transversais para a coleta dos dados de prevalência.…”
Section: Métodosunclassified
“…Os estudos que optaram por uma abordagem transversal 18,21,[27][28][29] apresentaram, em comum, a aplicação de questionários como elemento central para a busca dos resultados.…”
Section: Métodosunclassified
See 1 more Smart Citation